A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae) - Macgowan, Iain (Zootaxa, 2017)
Fulgenta gen. nov. is erected to include a group of Afrotropical species within the tribe Earomyiini on the basis of their distinctive male genitalia. Twelve new species are described within this new genus namely, Fulgenta apicalis MacGowan sp. nov., F. bilobata MacGowan sp. nov., F. complexa MacGowan sp. nov., F. excisa MacGowan sp. nov., F. freidbergi MacGowan sp. nov., F. geneti MacGowan sp. nov., F. longiphallus MacGowan sp. nov., F. plumosa MacGowan sp. nov., F. pretoria MacGowan sp. nov., F. saegeri MacGowan sp. nov., F. sangmelima MacGowan sp. nov. and F. setiphallus MacGowan sp. nov. Three previously described species, Lamprolonchaea lindneri Morge 1980, L. longicerca MacGowan, 2005 and L. ponti Morge, 1980 are re-assigned to Fulgenta. A revised key to the genera within the Earomyiini and a key to males of Fulgenta is provided.